Evaluation of Service Quality in Public Transportation using A Fuzzy Hybrid Method Based on SERVQUAL Approach: Istanbul Case Study - Buran, Büşra (Journal of Intelligent Systems in Current Computer Engineering, 2025)
Introduction Megacities are facing traffic jams and their negative effects such as economic, social, and environmental. Decision-makers and politicians want to decrease this pressure on cities by attracting public transportation. To make public transportation attractive, understanding passenger demand plays an important role. Another important issue is related to the increased service quality of the public transportation system. Methods In this study, to evaluate and increase the service quality of the public bus system, quality criteria are defined regarding EN13816 certification which is designed for public transport and logistic services. A hybrid fuzzy method consisting of two-level hierarchies was developed based on the SERVQUAL approach. A gap analysis was conducted to discover the gap score between the passenger and operator sides. A real case study is applied to the study which is the Istanbul bus transportation system. Results and Discussion The results show a gap between the passenger and operator sides except for availability criteria. The biggest gap is seen for the time criterion of service quality. When the passengers prioritize security criteria in public bus services, the operator focuses on time for the operation. This study contributes to the literature by providing the Analytic Hierarchy Process (AHP) using a Spherical Fuzzy Sets based on the Servqual approach which is a new solution due to preventing loss of information in complex problems. Conclusion Also, the study sheds on lights for the public bus authorities or operators to find out priority criteria in service quality for improving services.
Keywords: gap analysis